BACH1 deficiency improves placental angiogenesis via SLC25A51-mediated mitochondrial NAD+ transport in intrahepatic cholestasis of pregnancy - Shengpeng Li; Weiying Zhu; Zhixuan Xing; Dan Chen; Huimin Zhao; Yanli Zhang; Wenlong Zhang; Jiaojiao Sun; Yaxian Wu; Ling Ai; Qingfeng Pang (Molecular Medicine)
Abstract Background Placental angiogenesis is particularly important in the treatment of intrahepatic cholestasis of pregnancy (ICP). Although BACH1 has been implicated in angiogenesis associated with cardiovascular diseases, its specific role and underlying mechanisms in ICP remain unclear. This study aims to investigate the role of BACH1 in ICP. Methods The study used clinical samples and two distinct mouse models of ICP to validate BACH1 alterations in ICP through immunohistochemistry (IHC), immunofluorescence (IF), and western blot (WB) analyses. Subsequently, global BACH1-knockout mice were employed to investigate the phenotypic effects of BACH1 deficiency on ICP progression. The molecular mechanisms underlying the regulatory role of BACH1 in ICP were further elucidated using multi-omics approaches (e.g., transcriptomics and proteomics), combined with dual-luciferase reporter assays and electrophoretic mobility shift assays (EMSA). Results The expression of BACH1 was significantly upregulated in ICP, and its expression level positively correlated with clinicopathological indicators of ICP. Experiments using BACH1-knockout mice demonstrated that BACH1 deletion effectively ameliorated ICP-related placental tissue damage and significantly enhanced the expression levels of angiogenesis markers such as vascular endothelial growth factor (VEGF). Mechanistic investigations indicated that BACH1 deficiency activated the transcriptional expression of solute carrier family 25 member 51 (SLC25A51), thereby promoting the mitochondrial transport of nicotinamide adenine dinucleotide (NAD+), restoring mitochondrial function, and improving the activities of electron transport chain complexes I, II, and IV. Notably, BACH1 deficiency promoted taurocholic acid (TCA)-induced proliferation of human umbilical vein endothelial cells (HUVECs), whereas this phenotype could be reversed by shRNA-mediated knockdown of SLC25A51. Further studies confirmed that administration of the specific BACH1 inhibitor HPPE effectively alleviated TCA-induced suppression of HUVECs proliferation. Conclusions BACH1 may suppress placental angiogenesis by inhibiting the transcriptional expression of SLC25A51, making it a potential therapeutic target. Specifically, pharmacological inhibition of BACH1 could provide a targeted therapeutic strategy for placental angiogenesis associated with ICP. Graphical Abstract